ВПЛИВ НАНОЧАСТИНОК В ГАЗІ НА ПАРАМЕТРИ ПРЯМОЇ УДАРНОЇ ХВИЛІ - Avramenko, A.A.; Kobzar, A.S. (Institute of Engineering Thermophysics of NAS of Ukraine, 2024)
Using analytical analysis, the problem of passing gas with solid nanoparticles through a direct shock wave was solved. The problem is solved using the Rankine-Hugoniot approach. The influence of the concentration of nanoparticles in the gas, the heat capacity, and the density of the material of the nanoparticles on the parameters of the shock wave was revealed.